2022
DOI: 10.1523/eneuro.0045-22.2022
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for Paracrine Protective Role of Exogenous αA-Crystallin in Retinal Ganglion Cells

Abstract: Expression and secretion of neurotrophic factors have long been known as a key mechanism of neuroglial interaction in the central nervous system. In addition, several other intrinsic neuroprotective pathways have been described, including those involving small heat shock proteins such as α-crystallins. While initially considered as a purely intracellular mechanism, both αA-crystallins and αB-crystallins have been recently reported to be secreted by glial cells. While an anti-apoptotic effect of such secreted α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…It has been shown that phosphorylation of HspB4 at serine 148 (mice) and threonine 148 (human) is dramatically reduced in diabetic retinopathy, which could increase stress and apoptosis in retinal cells ( Ruebsam et al, 2018 ). HspB4 is highly expressed in Müller glia and protects retinal neurons via a paracrine mechanism ( Nath et al, 2022 ). Further, it has been shown that phosphorylation of threonine 148 in HspB4 enhances its cytoprotective function, which could reduce inflammation in the diabetic retina ( Nath et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that phosphorylation of HspB4 at serine 148 (mice) and threonine 148 (human) is dramatically reduced in diabetic retinopathy, which could increase stress and apoptosis in retinal cells ( Ruebsam et al, 2018 ). HspB4 is highly expressed in Müller glia and protects retinal neurons via a paracrine mechanism ( Nath et al, 2022 ). Further, it has been shown that phosphorylation of threonine 148 in HspB4 enhances its cytoprotective function, which could reduce inflammation in the diabetic retina ( Nath et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 47 , 48 Furthermore, retinal Müller cell-derived αA-crystallin was shown to have neuroprotective functions by anti-apoptotic effects in a paracrine manner. 49 Therefore, it is estimated that extracellular αB-crystallin from retinal Müller cells acts on adjacent cells to serve neuroprotective effects by paracrine, and IL-1β-mediated secretion reduction of αB-crystallin damages in the neural retina under diabetic conditions. As impairment of the neural function, such as the reduction of oscillatory potential amplitudes in electroretinograms, can be confirmed in patients with early diabetic retinopathy, 50 the reduction of extracellular αB-crystallin by IL-1β may have the potential to deteriorate the pathogenesis of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallin is a major protein of the lens and can be further categorized into α, β, and γ subtypes. It is also expressed in the retina [ 45 , 46 ]. Crystallin proteins are reported to be dramatically elevated in experimental autoimmune uveitis (EAU)-induced retinal mitochondrial protein, EAU-induced aqueous and vitreous protein, and EIU-induced vitreous protein profiles [ 15 , 47 , 48 ], and are suggested as potential biomarkers and therapeutic targets for uveitis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%